The Work Ethic In The West And In Islam - Yasien , Mohamed (الإحياء, 2024)
In this paper we compare the concept of the work ethic in the west with reference to the protestant work ethic of Max Weber and the work ethic in islam with special reference to the work ethic of al-Raghib al-isfahani (d. 1060).